Electrical Impedance Tomography for Biomedical Applications: Circuits and Systems Review - Wu, Yu; Hanzaee, Farnaz Fahimi; Jiang, Dai; Bayford, Richard H.; Demosthenous, Andreas (IEEE open journal of circuits and systems, 2021)
There has been considerable interest in electrical impedance tomography (EIT) to provide low-cost, radiation-free, real-time and wearable means for physiological status monitoring. To be competitive with other well-established imaging modalities, it is important to understand the requirements of the specific application and determine a suitable system design. This paper presents an overview of EIT circuits and systems including architectures, current drivers, analog front-end and demodulation circuits, with emphasis on integrated circuit implementations. Commonly used circuit topologies are detailed, and tradeoffs are discussed to aid in choosing an appropriate design based on the application and system priorities. The paper also describes a number of integrated EIT systems for biomedical applications, as well as discussing current challenges and possible future directions.